Impact of cold and flu medication on obstructive sleep apnoea and its underlying traits: A pilot randomized controlled trial. Issue 5 (24th January 2021) - Taranto‐Montemurro, Luigi; Sands, Scott; Azarbarzin, Ali; Calianese, Nicole; Vena, Daniel; Hess, Lauren; Kim, Sang‐Wook; White, David P.; Wellman, Andrew
ABSTRACT: Background and objective: Animal studies indicate that alpha‐1 adrenergic receptor agonists and antimuscarinic agents improve genioglossus muscle activity during sleep and may be candidates for the pharmacological treatment of OSA. On the other hand, noradrenergic stimulants may be wake‐promoting or cause insomnia symptoms if taken before bedtime, and the addition of a medication with sedative properties, such as an antihistaminic, may reduce these side effects. In this study, we aimed to determine the effects of the combination of an alpha‐1 adrenergic agonist (pseudoephedrine) and an antihistaminic‐antimuscarinic (diphenhydramine) on OSA severity (AHI), genioglossus responsiveness and other endotypic traits (Vpassive, muscle compensation, LG and arousal threshold). Methods: Ten OSA patients performed a randomized, placebo‐controlled, double‐blind, crossover trial comparing one night of pseudoephedrine 120 mg plus diphenhydramine 50 mg (DAW1033D) to placebo administered prior to sleep. The AHI, genioglossus muscle responsiveness to negative oesophageal pressure and the endotypic traits were measured via PSG. Results: The participants' median (interquartile range) age was 50 (46–53) years and body mass index (BMI) was 34.3 (30.6–39.2) kg/m 2 . The drug combination had no effect on AHI (21.6 (9.1–49.8) on placebo vs 37.9 (5.1–55.4) events/h on DAW1033D, P > 0.5) or genioglossus responsiveness (6.0 (2.6–9.2) on placebo vs 4.0 (3.5–7.3) %/cm H2 O). Amongst the phenotypic traits, only Vpassive was improved by 29 (3–55) % eupnoea, P = 0.03 (mean (95% CI)). Conclusion: The combination of pseudoephedrine and diphenhydramine did not improve OSA severity or genioglossus responsiveness but induced a small improvement in upper airway collapsibility, possibly due to the decongestant effect of the medications. The results of this study do not support the use of these medications for OSA treatment. Abstract : Pseudoephedrine and diphenhydramine, commonly used as over‐the‐counter combination for cold and flu, reduce the collapsibility of the upper airway in patients with OSA but do not reduce the number of obstructions. Their effect is not mediated by pharyngeal muscles stimulation, but most likely by a decongestant effect. See related Editorial